Are researchers following best storage practices for measuring soil biochemical properties? - Rhymes, Jennifer M.; Cordero, Irene; Chomel, Mathilde; Lavallee, Jocelyn M.; Straathof, Angela L.; Ashworth, Deborah; Langridge, Holly; Semchenko, Marina; de Vries, Franciska T.; Johnson, David; Bardgett, Richard D. (Soil, 2021)
It is widely accepted that the measurement of organic and inorganic forms of carbon (C) and nitrogen (N) in soils should be performed on fresh extracts taken from fresh soil samples. However, this is often not possible, and it is common practice to store samples (soils and/or extracts), despite a lack of guidance on best practice. We utilised a case study on a temperate grassland soil taken from different depths to demonstrate how differences in soil and/or soil extract storage temperature (4 or −20 ∘C) and duration can influence sample integrity for the quantification of soil-dissolved organic C and N (DOC and DON), extractable inorganic nitrogen (NH4+ and NO3-) and microbial biomass C and N (MBC and MBN). The appropriateness of different storage treatments varied between topsoils and subsoils, highlighting the need to consider appropriate storage methods based on soil depth and soil properties. In general, we found that storing soils and extracts by freezing at −20 ∘C was least effective at maintaining measured values of fresh material, whilst refrigerating (4 ∘C) soils for less than a week for DOC and DON and up to a year for MBC and MBN and refrigerating soil extracts for less than a week for NH4+ and NO3- did not jeopardise sample integrity. We discuss and provide the appropriate tools to ensure researchers consider best storage practice methods when designing and organising ecological research involving assessments of soil properties related to C and N cycling. We encourage researchers to use standardised methods where possible and to report their storage treatment (i.e. temperature, duration) when publishing findings on aspects of soil and ecosystem functioning. In the absence of published storage recommendations for a given soil type, we encourage researchers to conduct a pilot study and publish their findings.